2018
DOI: 10.1002/aoc.4758
|View full text |Cite
|
Sign up to set email alerts
|

Green chemical synthesis of Pd nanoparticles for use as efficient catalyst in Suzuki‐Miyaura cross‐coupling reaction

Abstract: Herein, we report the synthesis of tiny spherical Pd nanoparticles (NPs) by green chemical method under ambient conditions using flower extract of Lantana camara plant. The size of the Pd NPs is tunable from 4.7 to 6.3 nm by systematically controlling the concentration of either metal ions or plant extract. The synthesized Pd NPs were well characterized by different spectroscopic, microscopic and diffractometric techniques. The Pd NPs offered good size‐dependent catalytic activity in the Suzuki‐Miyaura C‐C cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 58 publications
(135 reference statements)
1
9
0
Order By: Relevance
“…This clearly indicated that a higher concentration of plant extract restricts the growth of particles during its formation and the presence of phytochemicals mainly composed of sugars, phospholipids, glycolipids, alkaloids, phenolics, tannins, etc. 35 assisted the particles to get aggregation in a particular orientation to form sponge-like structures. On the other hand, an inadequate amount of plant extracts results in the formation of isolated spherical CuO NPs.…”
Section: Microscopic Studymentioning
confidence: 99%
“…This clearly indicated that a higher concentration of plant extract restricts the growth of particles during its formation and the presence of phytochemicals mainly composed of sugars, phospholipids, glycolipids, alkaloids, phenolics, tannins, etc. 35 assisted the particles to get aggregation in a particular orientation to form sponge-like structures. On the other hand, an inadequate amount of plant extracts results in the formation of isolated spherical CuO NPs.…”
Section: Microscopic Studymentioning
confidence: 99%
“…There are many reports of palladium complexes supported on the surface of various solids such as magnetic nanoparticles and mesoporous materials (MCM‐41, MCM‐48 and SBA‐15). In particular, special attention has been paid to heterogeneous palladium catalysts because of their applications in carbon–carbon bond forming reactions such as Suzuki–Miyaura, Hatanaka, Hiyama, Stille, Espinet/Echavarren and Heck and Sonogashira reactions. It should be noted that there are only few reports describing complexes supported on the surface of boehmite for C–C bond formation .…”
Section: Introductionmentioning
confidence: 99%
“…The fine structure of 0.6Pd and 0.6Pd1.2Ga catalysts were observed by HRTEM, as shown in Figure (c) and (d). The lattice fringes of 0.6Pd catalyst display a interplanar spacing of 0.224 nm in the particle, which corresponds to the Pd (111) lattice plane . For 0.6Pd1.2Ga catalyst, Ga species are not reduced to metallic Ga after H 2 reduction, and Ga 2 O 3 neighbors with Pd nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The lattice fringes of 0.6Pd catalyst display a interplanar spacing of 0.224 nm in the particle, which corresponds to the Pd (111) lattice plane. [34] For 0.6Pd1.2Ga catalyst, Ga species are not reduced to metallic Ga after H 2 reduction, and Ga 2 O 3 neighbors with Pd nanoparticles. Figure 4, the 1.2Ga catalyst does not show any reduction peaks up to 700°C, indicating that Ga 2 O 3 species are reduced at higher temperatures.…”
Section: Structure Characterization Of the Catalystsmentioning
confidence: 95%